Formulation And Preliminary Validation Of The L-Karsa Model For Student Vocabulary Learning - Nia Astuti; M. Solehuddin; Nurlaili Nurlaili; Hilda Auliana; Zikra Zikra (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study was motivated by the low level of vocabulary mastery among elementary school students, which is caused by the dominance of teaching methods such as lectures, repetitive drills, and worksheet-based assignments that lack context and minimal interaction. This situation results in low early literacy skills among students in understanding and using vocabulary meaningfully. This study aims to formulate and preliminarily validate the L-KARSA Model (Socio-Cultural Augmented Reality Collaborative Literacy) as an innovative vocabulary learning model. The study employs a Design-Based Research (DBR) approach, implemented through the expert validation stage, encompassing needs analysis, model design, and prototype development. The research subjects consisted of elementary school teachers, first-grade students, and three expert validators. Data were collected through observation, interviews, and questionnaires, and analyzed using qualitative and quantitative approaches with the Content Validity Index (CVI). The results indicate that the L-KARSA Model was successfully formulated into six learning phases integrating collaborative literacy, Augmented Reality technology, and sociocultural values. Validation results showed that all items achieved an I-CVI ? 0.80 with an S-CVI/Ave of 1.00, falling into the “highly valid” category. These findings indicate that the L-KARSA model possesses strong theoretical and construct validity and has the potential to serve as an innovative alternative in contextual, interactive, and student-experience-based vocabulary learning. This study contributes to the development of a learning model based on the integration of technology and a sociocultural approach in the early literacy phase.